CRITICAL REVIEW OF CHRONIC DISEASE MANAGEMENT PROGRAMS AND EVALUATING EFFECTIVENESS AND SUSTAINABILITY IN ADDRESSING THE BURDEN OF NON-COMMUNICABLE DISEASES - 1Abdulrahman Abdulwahab Abbas Alsharief, 2Abdullah Ali A Alsharif, 3Abdelmohsen Abdelwahhab Abbas AlSharif, 4Abdulaziz Ali Faleh Alshahrani, 5Mohammed Ahmed Hussain Alsharif , 6Mohammed Douh Al Douh, (Chelonian Research Foundation, 2022)
Chronic disease management programs are crucial in addressing the growing burden of non-communicable diseases (NCDs) worldwide .This article surveys inveterate malady administration hones, looking at their viability and maintainability in tending to the burden of no communicable infections. A comprehensive writing audit assessed different angles of constant malady administration, counting techniques, benefits, and challenges. Techniques for evaluating the ampleness and adequacy of these government approaches are looked into, focusing on evidence-based intercession and long-term impacts. Advance discoveries through pictures, content, and visuals emphasize the role of constant malady treatment in moving forward well-being and lessening the burden of non-communicable infections. This article investigates the suggestions of these discoveries for clinical coordination, arranging, and counseling. In turn, the authors suggest changes in infection administration to proceed with the worldwide NCD epidemic. Keywords: Chronic disease management, non-communicable diseases, effectiveness, sustainability, healthcare delivery.